Control of microorganisms of oral health interest with Arctium lappa L. (burdock) extract non-cytotoxic to cell culture of macrophages (RAW 264.7) - Oliveira, Jonatas Rafael de [UNESP]; Aguiar Almeida, Rosilene Batista de [UNESP]; Figueiredo Vilela, Polyana das Gracas [UNESP]; Oliveira, Felipe Eduardo de [UNESP]; Rocha, Rosilene Fernandes da [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP]; Oliveira, Luciane Dias de [UNESP] (Elsevier B.V., 2014)
Objectives: To evaluate the antimicrobial activity of Arctium lappa L. extract on Staphylococcus aureus, S. epidermidis, Streptococcus mutans, Candida albicans, C. tropicalis and C. glabrata. In addition, the cytotoxicity of this extract was analyzed on macrophages (RAW 264.7).Design: By broth microdilution method, different concentrations of the extract (250-0.4 mg/mL) were used in order to determine the minimum microbicidal concentration (MMC) in planktonic cultures and the most effective concentration was used on biofilms on discs made of acrylic resin. The cytotoxicity A. lappa L. extract MMC was evaluated on RAW 264.7 by MTT assay and the quantification of IL-1 beta and TNF-alpha by ELISA.Results: The most effective concentration was 250 mg/mL and also promoted significant reduction (log(10)) in the biofilms of S. aureus (0.438 +/- 0.269), S. epiderrnidis (0.377 +/- 0.298), S. mutans (0.244 +/- 0.161) and C. albicans (0.746 +/- 0.209). Cell viability was similar to 100%. The production of IL-beta was similar to the control group (p > 0.05) and there was inhibition of TNF-alpha (p < 0.01).Conclusions: A. lappa L. extract was microbicidal for all the evaluated strains in planktonic cultures, microbiostatic for biofilms and not cytotoxic to the macrophages. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Arctium lappa; Biofilms; Staphylococcus; Streptococcus mutans; Candida; RAW 264.7